(untitled) (Global Journal of Human-Social Science, 2015)
This paper addresses the creation of pension funds for federal civil servants in Brazil, analyzing the existing legislation and regulation on this issue. To this end, it takes off based on the genesis of the Brazilian private pension plans, logging the emergence of private funds as well as the existence of various laws and constitutional amendments prior to Law 12,618/2012, which provided for the pension funds system for Brazilian federal public servants. It also identifies proponents and opponents to the Foundation for Pension Funds of Federal Civil Servants (FUNPRESP), signaling the discursive construction of the pension fund schemes as central character in contemporary welfare capitalism.